Principia Designae － Pre-Design, Design, and Post-Design Social Motive for the Highly Advanced Technological Society - Taura, Toshiharu (Springer Japan : Imprint: Springer, 2015)
This book presents a broad design purview within the framework of "pre-design, design, and post-design" by focusing on the "motive of design," which implies an underlying reason for the design of a product. The chapters are comprised of papers based on discussions at the "Design Research Leading Workshop" held in Nara, Japan, in 2013. This book encourages readers to enhance and expand their thinking within a widened design perspective.